2020
DOI: 10.37464/2020.373.98
|View full text |Cite
|
Sign up to set email alerts
|

Recognition for registered nurses supporting students on clinical placement: a grounded theory study

Abstract: Objective: This study examined registered nurses’ perspectives of being supportive of nursing students and providing them with learning opportunities when on clinical placements. Background: In Australia, as part of their three-year Bachelors degree, undergraduate nursing students undertake a minimum of 800 hours of clinical placement. During these clinical placement hours, nursing students are supervised by registered nurses who are required to be supportive of the students and provide them with learning opp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 15 publications
0
13
0
Order By: Relevance
“…The key finding in the majority of the studies were preceptorship is time‐consuming. Out of 14 papers included in this review, nine studies reported preceptorship as a time‐consuming activity (Anderson et al, 2020; Broadbent et al, 2014; Burke et al, 2016; Cassidy et al, 2012; Cusack et al, 2020; Haitana & Bland, 2011; Kalischuk et al, 2013; McCarthy & Murphy, 2010; Wu et al, 2016). Preceptors are supervising students along with their regular responsibility on the ward (Kalischuk et al, 2013).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The key finding in the majority of the studies were preceptorship is time‐consuming. Out of 14 papers included in this review, nine studies reported preceptorship as a time‐consuming activity (Anderson et al, 2020; Broadbent et al, 2014; Burke et al, 2016; Cassidy et al, 2012; Cusack et al, 2020; Haitana & Bland, 2011; Kalischuk et al, 2013; McCarthy & Murphy, 2010; Wu et al, 2016). Preceptors are supervising students along with their regular responsibility on the ward (Kalischuk et al, 2013).…”
Section: Resultsmentioning
confidence: 99%
“…Preceptors are supervising students along with their regular responsibility on the ward (Kalischuk et al, 2013). Anderson et al (2020) reports that supervising a student requires extra time and energy.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations